Deli Bakermart / Mohd. Azarul Mohd. Mokhtar... [et al.] - Mohd. Mokhtar, Mohd. Azarul; Kadri, Farah Ashikin; Illias, Nor Mazura; Baharudin, Sulhana; Saidin, Siti Norbayasauha (2000)
Deli Bakermart is a company supplying and selling raw materials & equipments for bakeries & pastries making. Our target markets comes form hotels, bakeries and shopkeepers and also individual customer This business operates in 45, 1st & 2nd Floor, Jalan Todak 4, Pusat Bandar Sunway, 13700 Seberang Jaya, Pulau Pinang.